2011
DOI: 10.1002/ccd.23352
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of cost‐saving and effectiveness of oral rapamycin plus bare‐metal stents with drug‐eluting stents: Three‐year outcome from the randomized oral rapamycin in Argentina (ORAR) III trial

Abstract: At 3 years follow-up, there were no differences in effectiveness between the two strategies, and DES strategy was not more cost-effective as compared to OR plus BMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…At the present time, in no TCAD patients, short‐term oral administration of either sirolimus or prednisone after PCI with BMS implantation demonstrated in all randomized clinical studies (seven), a significant reduction in restenosis and TVR compared to BMS alone . Furthermore, when compared with similar DES designs as authors used in the study , OI therapy showed similar clinical results to DES which were sustained at long‐term outcome .…”
supporting
confidence: 53%
“…At the present time, in no TCAD patients, short‐term oral administration of either sirolimus or prednisone after PCI with BMS implantation demonstrated in all randomized clinical studies (seven), a significant reduction in restenosis and TVR compared to BMS alone . Furthermore, when compared with similar DES designs as authors used in the study , OI therapy showed similar clinical results to DES which were sustained at long‐term outcome .…”
supporting
confidence: 53%
“…However, the drug-eluting benefit of EES may be attenuated by the use of chronic oral immunosuppression. As demonstrated in studies in native coronary disease, the use of oral immunosuppression with BMS resulted in improved stent patency, rates that were similar as with the use of DES [11][12][13]. A randomized control trial of BMS versus EES in the chronically immunosuppressed post-transplant population has not been done.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because oral immunosuppression may offset the drug-eluting benefit of DES. For instance, in the treatment of native coronary disease, the use of oral immunosuppression with BMS resulted in improved stent patency, rates that were similar as with the use of DES [11][12][13]. Furthermore, in spite of stenting with first-generation DES, redo transplantation occurred frequently, placing into question the utility of stenting as an option to delay retransplantation [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, after 3 years of follow‐up in humans, oral administration of rapamycin during the first 14 days following implantation of a BMS proved to be superior to BMS alone and had only minimal side effects, such as gum sores or diarrhoea . Importantly, it was also shown that this combination was as effective as the use of DES . As for indirect mTORC1 inhibitors, metformin is known to reduce neointimal formation through inhibition of SMC proliferation and migration as well as via potent induction of autophagy, making it the only anti‐diabetic drug with proven reduction of micro‐ and macrovascular complications in diabetic patients .…”
Section: Mtorc1 Inhibition In Atherosclerosismentioning
confidence: 99%